The level of occlusion of small saphenous vein after endovenous laser ablation - Anel Okić; Hasib Mujić; Amel Hadžimehmedagić; Nermina Babić; Alma Krvavac Hafizović; Azra Kajmaković Kožo (Medicinski glasnik, 2023)
Aim: To determine the success of endovenous laser ablation (EVLA) treatment and long-term occlusion of small saphenous vein (SSV), as well as factors and conditions that influence the effectiveness of EVLA treatment. Methods: A total of 250 patients treated with EVLA method over a period of seven years were followed one year after treatment. The main factors monitored and recorded during EVLA treatment were laser power (W), amount of delivered energy (J), duration of treatment (sec), veins length (cm), diameter (mm) and reflux (sec). Results: Within the first six months, the recanalization or insufficiently occluded SSV was noticed in ten, and after one year in one patient. The overall assessment of occlusion and satisfactory findings after one year of SSV was 95.6%. Conclusion: It is important to choose adequate power and the amount of delivered energy. The physician’s assessment and selection of an adequate patient greatly improves the outcome of the treatment. It is important to treat larger branches and double SSV between two fascias. Successful and effective EVLA treatment greatly reduces the possibility of recanalization of the treated vein.
Keywords: laser energy; laser power; occlusion; varicose vein